Sources of nonprotein-nitrogen as a substitute for protein in ruminant rations - Richardson, D.; Smith, E.F.; Perry, H.B.; Dunn, L.L.; Harbers, L.H. (Kansas Agricultural Experiment Station, 2011)
Americans consume large quantities of meat. An increasing population will demand more production to maintain present consumption rates. Protein is an essential nutrient for all animals. The simple-stomached animals (pigs, chickens, dogs, human beings, etc.) can utilize only natural protein, whereas ruminant animals can use nonprotein-nitrogen as a source of ammonia to produce microbial protein in the rumen. This project was to evaluate various ammoniated phosphates in ruminant rations.
Keywords: Beef; Non-protein nitrogen; Ammonia; Rations